Medical Therapy for Eisenmenger Syndrome: A Case Report and Review of Literature - Pradhan, Akshyaya; Vohra, Shweta; Vishwakarma, Pravesh; Sethi, Rishi (International Journal of Angiology, 2019)
Eisenmenger syndrome (ES) is defined as the process in which a long-standing left-to-right cardiac shunt caused by a congenital heart defect is eventually reversed into a cyanotic right-to-left shunt. It is crucial to recognize this grave pathology at the earliest because once it develops, treatment by medical or surgical means becomes even more challenging. In past decades, various therapeutic options have been developed that address the specific pathophysiological aspects of the disease and have shown to improve functional capacity and quality of life. There are three major therapeutic pathways in pulmonary hypertension treatment - endothelin receptor antagonists, phosphodiesterase type-5 inhibitors, and prostacyclin derivatives. These therapies not only improve hemodynamic parameters and exercise capacity but they also improve prognosis with various form of Pulmonary hypertension including ES. We report a case of a 35-year-old female of ostium secundum atrial septal defect with ES, started on upfront combination therapy of ambrisentan and tadalafil who demonstrated marked improvement after 3 months of medical therapy.
Keywords: ostium secundum atrial septal defect; pulmonary hypertension; endothelin–receptor antagonists; phosphodiesterase type-5 inhibitors; prostacyclin derivatives; echocardiography; Eisenmenger syndrome